1993
DOI: 10.1200/jco.1993.11.10.1969
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial of treatment with high-dose interleukin-2 either alone or in combination with interferon alfa-2a in patients with advanced melanoma.

Abstract: Using the preparation, dose, and schedule of IL-2 in our trial, IFN-alpha failed to enhance significantly the response rate to high-dose IL-2 in the treatment of patients with advanced melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(56 citation statements)
references
References 0 publications
1
53
0
2
Order By: Relevance
“…Biological therapy with combined IEN-a and IL-2 may result in synergistic interactions, with enhanced antigen presentation due to IFN-a-mediated up-regulation of class 1 MHC molecules and consequent improvement in tumour recognition by IL-2-stimulated cytotoxic T cells. In early non-randomized trials, the combination of both agents as sole therapy for metastatic melanoma appeared to be superior to either agent alone (Rosenberg et al, 1989), although this was not confirmed in a subsequent randomized phase III trial of high-dose intravenous IL-2 with or without IFN-a (Sparano et al, 1993). The addition of biological therapy with both IL-2 and IFN-a to chemotherapy may prove effective because of the lack of cross-resistance, as the mechanisms of resistance are different between these modes of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Biological therapy with combined IEN-a and IL-2 may result in synergistic interactions, with enhanced antigen presentation due to IFN-a-mediated up-regulation of class 1 MHC molecules and consequent improvement in tumour recognition by IL-2-stimulated cytotoxic T cells. In early non-randomized trials, the combination of both agents as sole therapy for metastatic melanoma appeared to be superior to either agent alone (Rosenberg et al, 1989), although this was not confirmed in a subsequent randomized phase III trial of high-dose intravenous IL-2 with or without IFN-a (Sparano et al, 1993). The addition of biological therapy with both IL-2 and IFN-a to chemotherapy may prove effective because of the lack of cross-resistance, as the mechanisms of resistance are different between these modes of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…An NCI Surgery Branch Study, administering high-dose bolus IL-2 (> 30 MIU m-2 day-') and IFN-a found the highest response rates (Rosenberg et al, 1989b). On the other hand, the Extramural IL-2 Working Group, using identical dose, schedule and patient selection criteria, did not observe any evidence of enhanced response with the IL-2/IFN-a combination (Sparano et al, 1993). In summary, a dose-response effect for IL-2 in the treatment of metastatic melanoma is not clear.…”
mentioning
confidence: 88%
“…However, low response rates of 10% or less were observed by others (Olham et al, 1992;Dillman et al, 1993;Sparano et al, 1993). The median response duration in these trials varied between 2 and 11 months, and the median survival was approximately 10 months (Lee et al, 1989;Rosenberg et al, 1989b;Oldham et al, 1992;Dillman et al, 1993;Sparano et al, 1993).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…IL-2, with or without lymphokine-activated killer cells, yielded response rates from 10-25% (Rosenberg et al, 1989a;Parkinson et al, 1990;Whitehead et al, 1991). With the combination of IL-2 and IFN-a the reported response rates varied between 0-44% (Rosenberg et al, 1989b;Dillman et al, 1993;Sparano et al, 1993;Keilholz et al, 1993;Kruit et al, 1995). A phase I-II study with increasing dose levels of bolus IL-2 and IFN-a produced an objective response in 33% of patients (Rosenberg et al, 1989b).…”
mentioning
confidence: 99%